Proposed an upgrading new interior design of kraftangan retail for Perbadanan Kraftangan Malaysia at No 63, Jalan Conlay, Kompleks Kraftangan Kuala Lumpur, 50450 Kuala Lumpur / Wirda Syuhada Mak Fol - Mak Fol, Wirda Syuhada (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to proposed an upgrading new interior design of kraftangan retail for Perbadanan Kraftangan Malaysia at no 63, jalan conlay, Kompleks Kraftangan Kuala Lumpur, 50450 Kuala Lumpur. This proposed upgrading kraftangan retail is to attract users, mostly on tourist to experience Malaysian identity and culture, at the same time to promote Malaysia unique craft product. The target market for the customer of this kraftangan retail range product is tourist from all over the world that are curious about Malaysia heritage. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact to the customer. Connected to that, the chosen design style for kraftangan retail is based on traditional Malay ethnic design, goes all the way with the client’s needs as they want the retail have the traditional Malay look and at the same time would attract the customers with different image. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is, type of product, spaces to be concluded in the proposed area, operation time and information about other retail that use the same system in management. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.